Praxeologie. Beiträge zur interdisziplinären Reichweite praxistheoretischer Ansätze in den Geistes- und Sozialwissenschaften - Weiser, Ulrich Wilhelm (Materiale Textkulturen, 2014)
'Praxeology' as theoretical concept has obtained growing attention in recent years, at the same time there is a lack of empirical findings upon its scope in applied research. The contributions of this volume prove the operational feasibility and heuristic capacity of the 'praxeological' approach in an interdisciplinary perspective and based on specific research questions.